2014
DOI: 10.1590/s0100-69162014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acoustic parameters for broiler welfare estimate

Abstract: ABSTRACT:Estimates of broiler welfare have subjective character. Nowadays, researchers seek non-invasive features or indicators that may describe this condition in animal production. The aim of this study was to identify acoustic parameters to estimate broiler welfare using the following five vocalization acoustic parameters: energy, spectral centroid, bandwidth, first formant, and second formant. The database that generated the model was obtained from a field experiment with 432 broilers, which half were Cobb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Distress calling appears not to be triggered directly by acute, startling stimuli (loud noise or electric shock [9]; air puff [10]), but rather discomfort or risky contexts: heat stress [11,12], cold stress [13], maternal signalling of threat [14], high density or food/water restriction (manipulated simultaneously [15]) or social isolation [2,9]. More generally, as young chicks are moved from the hatchery to the unfamiliar rearing environment, latency to settle and find resources and comfort is of critical welfare consideration [16], and distress calling is triggered by environmental unfamiliarity [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Distress calling appears not to be triggered directly by acute, startling stimuli (loud noise or electric shock [9]; air puff [10]), but rather discomfort or risky contexts: heat stress [11,12], cold stress [13], maternal signalling of threat [14], high density or food/water restriction (manipulated simultaneously [15]) or social isolation [2,9]. More generally, as young chicks are moved from the hatchery to the unfamiliar rearing environment, latency to settle and find resources and comfort is of critical welfare consideration [16], and distress calling is triggered by environmental unfamiliarity [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…By putting individual chicks into a climate-controlled chamber and altering the temperature, Moura et al (2008) showed that both the amplitude and the frequency of these calls increased when the temperature dropped. In farm conditions, heat stress leads to distinctive calls by both broilers (Pereira et al, 2014) and layers (Lee et al, 2015). Du et al (2018) monitored the number of vocalisations/bird both during the day and at night and argued that anomalies in this number of calls given by each bird, particularly at night, could be used for welfare assessment.…”
Section: Soundmentioning
confidence: 99%
“…They showed that when temperature decreased, the amplitude and frequency of the vocalizations increased as birds grouped together to reduce heat loss, while during thermal comfort the amplitude and frequency of vocalizations stabilized. Pereira et al [39] identified thermal stress conditions based on broiler vocalizations and verified the existence of different vocalization patterns in heat stressed birds. In this case, the study was based on four vocalization acoustic parameters: energy, bandwidth, and first and second formant (using Praat ® and Matlab ® software).…”
Section: Sensorsmentioning
confidence: 99%